2016
DOI: 10.1126/scitranslmed.aag0976
|View full text |Cite
|
Sign up to set email alerts
|

AZD3759, a BBB-penetrating EGFR inhibitor for the treatment of EGFR mutant NSCLC with CNS metastases

Abstract: Non-small-cell lung cancer patients with activating mutations in epidermal growth factor receptor (EGFR) respond to EGFR tyrosine kinase inhibitor (TKI) treatment. Nevertheless, patients often develop central nervous system (CNS) metastases during treatment, even when their extracranial tumors are still under control. In the absence of effective options, much higher doses of EGFR TKIs have been attempted clinically, with the goal of achieving high enough drug concentrations within the CNS. Although limited tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 40 publications
(44 reference statements)
4
67
0
1
Order By: Relevance
“…AEE788 and dacomitinib, which have no previous reports regarding their efflux transporter liability, were shown to be substrates of both/ either P-gp and/or Bcrp in this study (see the DA values in Table 4). The K p,brain in TKO for AZD3759 was similar to the value in wild-type, with a DA of 1.56, which indicates neither P-gp nor Bcrp plays a major role in the brain distribution of AZD3759, as was previously reported (Zeng et al, 2015;Yang et al, 2016). In conclusion, seven out of eight EGFR inhibitors investigated in the current study were shown to be substrates of both/either P-gp and/or Bcrp based on the DA calculated with the brain partition coefficients in wild-type and TKO mice, and AZD3759 is the only exception that is not a substrate of both P-gp and Bcrp.…”
Section: Discussionsupporting
confidence: 77%
“…AEE788 and dacomitinib, which have no previous reports regarding their efflux transporter liability, were shown to be substrates of both/ either P-gp and/or Bcrp in this study (see the DA values in Table 4). The K p,brain in TKO for AZD3759 was similar to the value in wild-type, with a DA of 1.56, which indicates neither P-gp nor Bcrp plays a major role in the brain distribution of AZD3759, as was previously reported (Zeng et al, 2015;Yang et al, 2016). In conclusion, seven out of eight EGFR inhibitors investigated in the current study were shown to be substrates of both/either P-gp and/or Bcrp based on the DA calculated with the brain partition coefficients in wild-type and TKO mice, and AZD3759 is the only exception that is not a substrate of both P-gp and Bcrp.…”
Section: Discussionsupporting
confidence: 77%
“…AZD3759 represents a novel class of EGFR‐TKI, which is not a substrate of the efflux transporters P‐gp or BCRP. This compound, which was specifically developed to achieve high exposure both in the plasma and in the CNS by penetrating the BBB, is under investigation for the treatment of CNS metastases from NSCLC . AZD3759 has an unbound brain exposure:unbound plasma ratio of 0.86, indicating similar free exposure in the brain and plasma .…”
Section: Egfr‐tkismentioning
confidence: 99%
“…In contrast to the negative clinical results in BM, radiosensitizing effect of EGFR‐TKIs was reported in extracranial tumors in both clinical and preclinical settings, suggesting the potential of combining a BBB‐penetrating agent with radiation for BM. AZD3759 was an EGFR‐TKIs with good BBB penetration in both preclinical and clinical settings, and showed promising activity in patients with central nervous system (CNS) metastasis as monotherapy . In our study, we evaluated the potential of AZD3759 in combination with radiation in a BM model in mice, and explored the mechanism underneath.…”
Section: Introductionmentioning
confidence: 99%